Kajian Literatur Optimalisasi Sistem Transdermal Patch untuk Terapi Antinyeri - Aulia Setia Putri; Ayumi Tresna Laksmi Putri; Bilqis Vanessa Zattaniya; Deshita Putri Nurrisma; Ryan Hidayat; Saiful Rizal; Dwintha Lestari (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Pain therapy requires a drug delivery system capable of maintaining a stable analgesic effect with minimal adverse effects; therefore, transdermal patch systems represent a promising alternative. This literature review aims to analyze optimization strategies of transdermal patches to enhance the effectiveness of pain therapy. The method employed was a systematic narrative literature review of articles published between 2015 and 2025, retrieved from Google Scholar, PubMed, ScienceDirect, and MDPI databases. Article selection was conducted based on relevance to formulation, evaluation, and effectiveness of transdermal patches for analgesic therapy, resulting in a total of 18 articles included in the analysis. Comparative synthesis of the literature identified three main pillars of optimization: the use of natural active compounds with analgesic and anti-inflammatory potential, the application of chemical penetration enhancers (CPEs), and the implementation of physical enhancement technologies. Active compounds such as piperine and flavonoids demonstrated good compatibility within patch systems, while CPEs such as sodium lauryl sulfate and propylene glycol were reported to increase drug permeation by approximately 2–5 times compared to formulations without enhancers. Physical technologies, including microneedles, sonophoresis, and iontophoresis, were selected for their ability to mechanically reduce the barrier function of the stratum corneum, thereby supporting controlled drug release and producing a stable pharmacokinetic profile characterized by gradual release and maintenance of drug concentrations within the therapeutic range. Although the findings indicate that integrating these three optimization pillars may enhance analgesic effectiveness and patient adherence, this review is limited by the predominance of preclinical studies and methodological heterogeneity. Therefore, further validation through large-scale clinical trials is required to support the achievement of transdermal patch optimization in clinical pain management.